Rural teachers training and agricultural development in the stroessner’s dictatorship (2016)
Between the fifties and seventies the dictatorship of Alfredo Stroessner executed an unprecedented expansion of all educational levels, by implementing reforms and innovations in content and infrastructure of the Paraguayan educational system, with emphasis on teacher training in rural areas. These transformations were performed under the watchful guidance of US cooperation agencies, which implemened similar policies in the region as part of its geopolitical project of the moment. These educational policies went hand in hand with the modernization of the agrarian structure of the country. In Paraguay, there is no research into the implications of this relationship. However, through analysis of unpublished documents from the library of the Higher Institute of Education, we can develop, in a preliminary manner, the ideological justifications that legitimize the modernization of the agrarian structure through the educational system. Understanding the link between the agrarian structure and educational policies is fundamental to a critical interpretation of the current period of democratic transition, whose limitations come from the authoritarian political system established in the country for so many decades.